2014
DOI: 10.1007/s10461-014-0970-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Apathy Among People Living with HIV: Implications for Treatment of HIV Associated Neurocognitive Disorders

Abstract: Depression and apathy are common among people living with HIV (PLWH). However, in PLWH, it is unclear whether depression and apathy are distinct conditions, which contribute to different patterns of disruption to cognitive processing and brain systems. Understanding these conditions may enable the development of prognostic indicators for HIV associated neurocognitive disorders (HAND). The present study examined substance use behavior and cognitive deficits, associated with depression and apathy, in 120 PLWH, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 49 publications
0
17
2
1
Order By: Relevance
“…Noteworthy, apathy is significantly associated with high HIV-1 plasma levels and poor neurocognitive performance in HIV-1-infected individuals (Shapiro et al, 2013). Moreover, depression and apathy are hallmarks of HIV-1 patients with a history of cocaine or alcohol abuse (Bryant et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, apathy is significantly associated with high HIV-1 plasma levels and poor neurocognitive performance in HIV-1-infected individuals (Shapiro et al, 2013). Moreover, depression and apathy are hallmarks of HIV-1 patients with a history of cocaine or alcohol abuse (Bryant et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described the specific comorbid effects of depression within chronic disease populations. For example, studies have shown that depression is associated with cognitive decline, faster disease progression, and increased mortality in persons living with HIV (Bryant et al, 2015; Rivera-Rivera et al, 2016). Among persons living with cancer, depression often worsens other cancer symptoms and results in more symptom interference, poor adherence, and worse outcomes and survival (Kim et al, 2015; Stanton et al, 2018; Zimmaro et al, 2018).…”
Section: Increased Depressive Symptoms In Persons With Comorbid Condimentioning
confidence: 99%
“…Multiple studies have indicated that adults with HIV and depression as well as post-traumatic stress disorder were more likely to experience cognitive impairments (Bryant et al, 2015; Rubin et al, 2016). Fortunately, studies have also suggested that if emotional health is restored through pharmacological or non-pharmacological treatments, cognitive function rebounds (Bryant et al, 2015).…”
Section: Lifestyle Factors Brain Health and Cognitionmentioning
confidence: 99%
“…Fortunately, studies have also suggested that if emotional health is restored through pharmacological or non-pharmacological treatments, cognitive function rebounds (Bryant et al, 2015). This highlights the need to address emotional health in this clinical population.…”
Section: Lifestyle Factors Brain Health and Cognitionmentioning
confidence: 99%